Inpatient outcomes of upper cervical fractures in the elderly: a retrospective analysis of 268 cases - Nicolas H. von der Höh; Jonathan Keuchel; Phillip Pieroh; Ulrich Josef Albert Spiegl; Georg Osterhoff; Christoph-Eckhard Heyde (BMC Geriatrics)
Abstract Background The incidence of upper cervical fractures in elderly individuals is increasing, necessitating enhanced treatment approaches. Method A retrospective study of 268 elderly patients with upper cervical fractures was conducted to assess inpatient outcomes aged 75 and older with atlas and/or axis fractures. Patient risk was evaluated using the ASA score and Charlson comorbidity index (CCI). In-hospital mortality and functional outcomes were assessed, with fracture treatment strategies following AO principles. Results Patients with C1, C2 or combined fractures did not differ in age, CCI, Barthel score or length of hospital stay (p > 0.05). C2 fractures were predominant, and the majority of patients suffered at least from a severe general disease (ASA ≥ 3). Comparing operatively and conservatively treated patients, regardless of fracture localization, revealed no significant differences in mortality, both overall and time-related. Surgical patients experienced a higher frequency of general complications, notably dyspnea. The overall mortality rate was 14.9%, with 15.7% in the nonoperative group and 14.4% in the surgical group (p = 0.8628). The overall rate of general complications was 51.4% (n = 51) in the nonoperative group and 71.9% (n = 110) in the operatively treated group. Anterior fixation procedures showed significantly higher rates of pneumonia and respiratory complications, while mortality and other complications did not differ significantly between posterior and anterior surgical approaches. Conclusion The in-hospital mortality and morbidity of elderly patients with upper cervical fractures are high but do not significantly differ between operatively and nonoperatively treated patients. The complexity of the geriatric patient population highlights the need for peri- and postinpatient geriatric complex treatment, emphasizing the importance of establishing geriatric-specialized care structures.